การจำลองเซลล์เชื้อเพลิงแบบเยื่อแผ่นแลกเปลี่ยนโปรตอน - ฐิติกร วาสนาเพียรพงศ์ (จุฬาลงกรณ์มหาวิทยาลัย, 2003)
The mathematical model for simulating a proton exchange membrane fuel cell is divided to two sections. The first section was to develop mathematical model for flow behavior in fuel cell by using a computational fluid dynamics (CFD) technique in Fluent 4.5. The result in this section will predict gas and water distribution in the cell. The second section, the results from the first part were transformed to empirical models for using in Aspen Plus, the program for simulating general chemical processes. The advantage of the fuel cell model in Aspen Plus compared with that in Fluent 4.5 is that the Aspen model can be compuled much faster and it also can be used to simulate together with other units such as humidifier and reformer unit.